Mutations in the bZIP domain of yeast GCN4 that alter DNA-binding specificity. - Tzamarias, D (1992)
The bZIP class of eukaryotic transcriptional regulators utilize a distinct structural motif that consists of a leucine zipper that mediates dimerization and an adjacent basic region that directly contacts DNA. Although models of the protein-DNA complex have been proposed, the basis of DNA-binding specificity is essentially unknown. By genetically selecting for derivatives of yeast GCN4 that activate transcription from promoters containing mutant binding sites, we isolate an altered-specificity mutant in which the invariant asparagine in the basic region of bZIP proteins (Asn-235) has been changed to tryptophan. Wild-type GCN4 binds the optimal site (ATGACTCAT) with much higher affinity than the mutant site (TTGACTCAA), whereas the Trp-235 protein binds these sites with similar affinity. Moreover, the Trp-235, Ala-235, and Gln-235 derivatives differ from GCN4 in their strong discrimination against GTGACTCAC. These results suggest a direct interaction between Asn-235 and the +/- 4 position of the DNA target site and are discussed in terms of the scissors-grip and induced-fork models of bZIP proteins.